2006
DOI: 10.1016/j.jcrs.2006.04.046
|View full text |Cite
|
Sign up to set email alerts
|

Measuring total corneal power before and after laser in situ keratomileusis with high-speed optical coherence tomography

Abstract: PURPOSE: To measure total corneal power using optical coherence tomography (OCT). SETTING:Refractive surgery practices at 2 academic eye centers in Cleveland, Ohio, and Los Angeles, California, USA. METHODS:Thirty-two eyes of 17 patients having myopic laser in situ keratomileusis (LASIK) were enrolled in a prospective observational study. Manifest refraction, OCT, and Placido ring corneal topography with the Atlas 995 (Carl Zeiss Meditec, Inc.) were performed preoperatively and 3 months after laser in situ ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 23 publications
2
85
0
2
Order By: Relevance
“…Anterior segment optical coherence tomography (AS-OCT) can measure the entire shape of both corneal surfaces with a nearinfrared light 15 without image degradation when there is corneal opacity. 16 Recent studies 17,18 found that the topography and CCT data obtained using AS-OCT agree well with conventional measurements.…”
mentioning
confidence: 70%
“…Anterior segment optical coherence tomography (AS-OCT) can measure the entire shape of both corneal surfaces with a nearinfrared light 15 without image degradation when there is corneal opacity. 16 Recent studies 17,18 found that the topography and CCT data obtained using AS-OCT agree well with conventional measurements.…”
mentioning
confidence: 70%
“…In a preliminary study, Savini, et al [6] reported that the Total Refractive Power (the power determined by corneal ray tracing, in which Snell's law and specific indices of air, the cornea and the aqueous are used) on the Pentacam HR seems to be an accurate method to evaluate surgically induced refractive changes. Using high-speed optical coherence tomography (OCT), Tang [1] found that the difference between total power for 3.0 mm and 4.0 mm zones (calculated by the radius of the corneal anterior surface and posterior surface with the real corneal index of 1.376) changes, and LASIK-induced refraction changes is 0.16 D with a correlation coefficient of 0.94, while simulated keratometry underestimated refraction the change by 0.60 D, 18.9% by linear regression. Therefore, these investigators concluded that measuring both anterior and posterior corneal surfaces with a combination of OCT and Placido ring topography provided a better measure of total corneal power that closely tracked the surgically induced refractive changes.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal changes given by corneal topographies are generally believed to underestimate the actual surgically induced refractive changes [1]. Several explanations, such as the invalid keratometric refraction index of 1.3375 [1,2], the change in posterior surface [3,4] and corneal index change after refractive surgery [5] were proposed to explain this phenomenon. Subsequently, different methods [6][7][8] to accurately assess the refractive changes have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 32 eyes from 17 LASIK patients, we evaluated the repeatability of OCT-based corneal power measurement by pooled standard deviation [61]. The repeatability is 0.79D for the anterior surface and 0.10D for the posterior surface.…”
Section: Measuring Corneal Refractive Powermentioning
confidence: 99%
“…At 2,000 axial scan per second, eye movement during OCT scans still produces noticeable error in corneal power measurement. Nevertheless, if we combine the OCT-measured pachymetry map and anterior corneal topography, the resulting total corneal power can closely track the refractive change after LASIK [61].…”
Section: Measuring Corneal Refractive Powermentioning
confidence: 99%